The Country, the City, and the Corporation: Rio Tinto Kennecott and the Materiality of Corporate Rhetoric. Issue 6 (18th August 2018) - Paliewicz, Nicholas S.
ABSTRACT: Contributing to extant discourses about corporate environmental advocacy, this paper argues that corporations can embed discursive rhetorical strategies in material places and spaces. This argument contributes to environmental communication by bridging divisions between discursive and materialist approaches to corporate rhetoric. Corporate materiality is realized in the study of Rio Tinto Kennecott (RTK) at places of corporate community where RTK enunciates a dominant environmental discourse about the necessity of the Bingham Canyon Mine through strategies such as the technological shell game, the hypocrite's trap, and corporate heterotopia, which are made manifest materially alongside cultural values such as epistemic trust, technological progress, community, and home. Using participatory critical rhetoric as a methodology, I analyse RTK's material rhetoric at the Natural History Museum of Utah, the Rio Tinto Soccer Stadium, and the Daybreak suburban community. This case study reveals that corporations are assemblages that assert many different, and sometimes competing, arguments that can deflect environmental criticism, materially.